ANALYSIS AND IMPACT OF APIA ACTIVITY ON DEVELOPMENT AND SUPPORT OF AGRICULTURAL SECTOR IN ROMANIA - COPĂCEANU, Cristina; MAZĂRE, Silvia (Journal of Social Sciences)
Agriculture is a very important sector for Romania, providing food and products of vegetable and animal origin, jobs for people in villages and business opportunities for enterprises and investors. Romania's agricultural area is in permanent change, influenced by European money that was attracted through support measures and community policies, and environmental protection and the need to ensure a sustainable development of agriculture in Romania made the activity of the Agency for Payments and Intervention for Agriculture (APIA) stands out as an important factor in aligning modern agriculture with the environment. Through this study, we aim to analyze the way in which APIA promotes sustainable agricultural practices and provides support to farmers to protect the environment and whether the agency's activity has brought benefits to the economic development of Romania and Neamț County. We thus demonstrate the important role that the agency has for the economy, for supporting farmers and agricultural producers in Romania, but also for the country's agricultural policy, the institution participating in the development and implementation of national agricultural policies and strategies, as well as in the process of negotiating subsidies and projects within the European Union (EU) agricultural financing system.